2006
DOI: 10.1098/rsbl.2006.0449
|View full text |Cite
|
Sign up to set email alerts
|

Sperm design and sperm function

Abstract: Spermatozoa vary enormously in their form and dimensions, both between and within species, yet how this variation translates into fertilizing efficiency is not known. Sperm swimming velocity is a key determinant of male fertilization success, but previous efforts to identity which sperm phenotypic traits are associated with swimming velocity have been unsuccessful. Here, we examine the relationship between the size of several sperm components and sperm swimming velocity in natural populations of red deer (Cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
212
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(223 citation statements)
references
References 19 publications
6
212
2
3
Order By: Relevance
“…Spermatozoa with elongated heads are faster than those with round heads (Malo et al 2006). Research in dogs by Rijsselaere et al (2004) has shown that sperm concentration influences sperm dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa with elongated heads are faster than those with round heads (Malo et al 2006). Research in dogs by Rijsselaere et al (2004) has shown that sperm concentration influences sperm dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in head dimensions may affect hydrodynamic resistance, therefore resulting in a more hydrodynamically efficient sperm design (Malo et al 2006, Gillies et al 2009). Furthermore, the increase in sperm HA is associated with the appearance of a hook.…”
Section: Discussionmentioning
confidence: 99%
“…Besides methodological issues, different hypotheses have been proposed to explain which are the first evolutionary steps that lead to early increases in sperm swimming velocity. An intraspecific study on red deer showed that an elongation of the sperm head was associated with an increase in sperm swimming speed, suggesting that elongated sperm heads experience a reduction in drag and make sperm more hydrodynamically efficient (Malo et al 2006). Alternatively, a comparative study on a closely related group of cichlid fish found an evolutionary disassociation between increases in sperm swimming speed in response to sperm competition and the size of the sperm, and postulated that the first steps may involve increases in energy production which precede any changes in sperm dimensions (Fitzpatrick et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Malo et al (2006) reported a negative phenotypic correlation between midpiece length and VAP in red deer, whereas Mossman et al (2009) have recently reported a negative genetic correlation between midpiece length and sperm velocity in zebra finches. Similarly, Firman and Simmons (2008) showed that in house mice sperm length (including the midpiece) was negatively associated with competitive fertilization success, although in that species midpiece length appears to be positively associated with sperm swimming velocity (Firman and Simmons, 2010).…”
Section: Jp Evansmentioning
confidence: 99%